2015
DOI: 10.4149/neo_2015_002
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of TGF-β in Epithelial–Mesenchymal Transition (EMT): Down-regulation of E-cadherin via snail

Abstract: TGF-β plays a central role in epithelial-mesenchymal transition (EMT), which is a highly conserved and reversible process that governs tumor development, invasion and metastasis. Through this transition, the epithelial cell acquires a migratory behavior which allows it to move away from the cell community and to integrate into the surrounding tissue. The cells lost epithelial phenotypes including the change of cell polarity and the loss of specialized cell-cell contacts, which related with the shortage of E-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 133 publications
2
52
0
2
Order By: Relevance
“…Evidences from these studies confirmed that epithelial cells expressed high levels of E-cad, and E-cad was down-regulated whereas N-cadherin was up-regulated during the process of EMT [2, 7]. Therefore, in this study, the expression levels of E-cad and N-cad were determined by Western blotting (Figure 2A).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Evidences from these studies confirmed that epithelial cells expressed high levels of E-cad, and E-cad was down-regulated whereas N-cadherin was up-regulated during the process of EMT [2, 7]. Therefore, in this study, the expression levels of E-cad and N-cad were determined by Western blotting (Figure 2A).…”
Section: Resultssupporting
confidence: 59%
“…Recently, the epithelial-mesenchymal transition (EMT) has been recognized as a new source contributing to cancer cell migration and metastasis. Tumor cells progress from non-invasive to malignant phenotypes via a series of critical steps that involve morphological changes referred to as the EMT [2, 3]. EMT which is characterized by the loss of apical basal polarity and tight cell-cell adhesions of epithelial cells and the acquiring of anterior-posterior polarity, migratory and invasive behaviors of mesenchymal cells [4], has been confirmed to play a central role in metastasis of cancers [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…By inducing Snail, TGF- signaling promotes cell migration [78]. This factor is also associated with EMT [78,79] through Kindle-2 upregulation in pancreatic ductal adenocarcinoma [80].…”
Section: Discussionmentioning
confidence: 98%
“…The occurrence of EMT involved the regulation of many genes, and several studies have implied the importance of E-cadherin and Snail in regulating EMT [16, 17], and these EMT-associated transcription factors are the potential targets for traditional Chinese medicine. Further studies have shown that JPJD inhibited TGF- β -induced EMT by downregulating the mRNA expression of Snail and upregulating the mRNA expression of E-cadherin, and JPJD inhibited the mRNA expression of E-cadherin by suppressing the promoter activity of CDH1 gene, which encoded E-cadherin protein.…”
Section: Discussionmentioning
confidence: 99%